2005
DOI: 10.1002/cncr.20739
|View full text |Cite
|
Sign up to set email alerts
|

Prostate carcinoma detection and increased prostate‐specific antigen levels after 4 years in Dutch and Japanese males who had no evidence of disease at initial screening

Abstract: The risk of developing prostate carcinoma within a given 4-year period is greater for Dutch males ages 55-69 years compared with their Japanese counterparts, because the former have higher PSA levels. Nonetheless, there appears to be no significant difference in prostate carcinoma risk between Dutch and Japanese males whose baseline PSA levels fall within the same range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 7 publications
4
21
2
Order By: Relevance
“…31 A previous study compared the probability of freedom from PSA increases to levels greater than 4.0 ng/ml between Dutch and Japanese males. 35 Although there were statistically significant differences in mean PSA levels and the distribution of PSA levels between these two ethnic groups, the probability of PSA progression to greater than 4.0 ng/ml was not statistically significantly different between Dutch and Japanese males controlling for age and baseline PSA level. Our findings are similar in that despite finding differences in PSA levels between black and white males, the likelihood of conversion to PSA greater than 4.0 is not significantly different between the two ethnic groups.…”
Section: Discussionmentioning
confidence: 75%
“…31 A previous study compared the probability of freedom from PSA increases to levels greater than 4.0 ng/ml between Dutch and Japanese males. 35 Although there were statistically significant differences in mean PSA levels and the distribution of PSA levels between these two ethnic groups, the probability of PSA progression to greater than 4.0 ng/ml was not statistically significantly different between Dutch and Japanese males controlling for age and baseline PSA level. Our findings are similar in that despite finding differences in PSA levels between black and white males, the likelihood of conversion to PSA greater than 4.0 is not significantly different between the two ethnic groups.…”
Section: Discussionmentioning
confidence: 75%
“…More recently, studies have shown that the baseline PSA level can predict the risk of developing prostate cancer, and one Japanese study showed that the baseline PSA levels in Japan from 1988 to 2003 remained stable over 16 years [8][9][10][11] . Therefore, we investigated the yearly changes in the baseline PSA levels in our hospital to determine the number of men with prostate cancer detected at periodic health exams at a health promotion center at our hospital from 1995 to 2008.…”
Section: Prostate Cancer In Koreamentioning
confidence: 99%
“…Third, the PC risk calculator used to estimate “RC‐based AIR” was based on data collected in European Randomized Study of Screening for Prostate Cancer (ERSPC) and may not be generalizable to the Japanese population. Most importantly, a previous international cooperative study of Dutch and Japanese men demonstrated that the risk for developing PC may be identical given similar baseline PSA levels . Furthermore, we performed a head to head comparison between our original predictive nomogram and the ERSPC nomogram using the same Japanese population data .…”
Section: Discussionmentioning
confidence: 99%